Refining the phylogeny of Crambidae with complete sampling of subfamilies (Lepidoptera, Pyraloidea) - Léger, Théo; Mally, Richard; Neinhuis, Christoph; Nuss, Matthias (Zoologica scripta, 2021)
Crambidae is a group of moths with more than 10,000 species occurring worldwide that evolved diverse morphological and ecological habits. They can be best recognized by morphological characters of the adult tympanal organ and larval chaetotaxy. We present the first molecular phylogeny of Crambidae including all subfamilies and most tribes. We use available molecular data from two previous studies, and published transcriptomes and genomes, compiling ten genes totalling 11,247 bp. Up to eight genes are sequenced for thirty‐nine additional taxa, with Cathariinae, Cybalomiinae and Linostinae sampled for the first time. Maximum‐likelihood and Bayesian analyses recover topologies mostly agreeing with those of previous studies, with several groupings showing better support. Cathariinae syn. n. and Cybalomiinae syn. n. are recovered as ingroup of Glaphyriinae and are consequently synonymized with the latter. Linostinae are either sister to Glaphyriinae or sister to the ‘CAMMSS clade’. Lathrotelinae are recovered monophyletic and as sister to Musotiminae in the Bayesian analysis. Hoploscopinae stat. n. are recovered as sister to ((Crambinae + Erupinae stat. n.) + (Scopariinae + Heliothelinae s. str.)). Evolution of host‐plant preferences is discussed.